Solar Tracking System Pada Panel Surya dengan Metode Optimum Tegangan Menggunakan Mikrokontroler - Habsari, Kumala Mahda; Arwin, Zawatan; Ningrum, Hanifah Nur Kumala; Prakoso, Dimas Nur (Elposys: Jurnal Sistem Kelistrikan, 2025)
This study examines the application of a Solar Tracking System on photovoltaic panels using the Optimal Voltage Method controlled by an Arduino Mega 2560 microcontroller. The system is designed to dynamically optimize the panel's position to continuously face the sun, thereby increasing radiation absorption and improving electrical energy conversion efficiency. Testing was conducted by comparing the output voltage of the panel with and without the tracking system. The measurement results showed an average increase of 1.51% in the output voltage when the tracking system was activated. Analysis of solar irradiation data and light intensity further supports the system's effectiveness in maximizing solar energy utilization throughout the day. With the Arduino Mega 2560's ability to process data in real-time and control linear actuators, this system has proven to be effective in enhancing photovoltaic panel performance. This research is expected to lead to significant changes. The innovation made can improve solar energy efficiency, reduce costs, and expand global access to clean energy. Furthermore, this innovation contributes to achieving sustainability goals set by various countries, creating a positive impact on economic growth, job creation, and environmental health. With ongoing technological advancements, the solar tracking system has the potential to play a key role in realizing a more sustainable and environmentally friendly future in the energy sector.